Effects of Concussion in Adolescent Students: Perceptions and Performance. (28th May 2019) - Rieger, Brian; Lewandowski, Lawrence; Potts, Heather; Shea, Nicole
Abstract: Objective: The purpose of this study was to compare adolescent students with and without concussion on a battery of academic, neurocognitive, and socioemotional measures and assess the aftereffects of concussion across domains of functioning.Methods: Twenty-four adolescents (ages 13–17) reporting postconcussion symptoms were compared to 24 controls matched for age and gender across a battery of tests and surveys.Results: After correcting for multiple comparisons, there were no significant differences on any neuropsychological measures. Similarly, there were no significant group differences on academic measures of vocabulary, word recognition, or reading comprehension. Self-reported concussion symptoms were much greater for students with concussion, as were self-reports of anxiety, depression, and somatization symptoms. Parents also rated those with concussion as having greater depression and somatization symptoms, but not to a degree that survived Bonferroni correction. Lastly, those with concussion reported a significantly greater number of school problems and academic concerns.Conclusions: Results indicated that adolescents who reported postconcussion symptoms do not perform differently from peers on most neurocognitive and academic tasks, yet they showed considerably more worry, somatization, academic concerns, and feelings of inadequacy than matched controls. The findings suggest that interventions to address psychological and academic stress may be indicated for adolescents symptomatic from concussion.